Usuvabadus kõigile: baptismi and ja vastutus - Peck, Anthony (Usuteaduslik Ajakiri, 2021)
Religious Freedom for All – Baptist Gift and Responsibility The earliest English Baptists of the 17th century were among the first to argue for universal religious freedom in the face of state-imposed religious conformity. This article examines the origins of that conviction in English Separatism and continental Anabaptist thought. It discusses the challenges that such a conviction brought, to the religious situation of the time, to succeeding generations of Baptists themselves, and to the contemporary situation of religious freedom around the world. The subsequent development of the idea of religious freedom for all among the Baptists is explored, including the importance of keeping in balance the three elements of the rule of Christ, natural rights, and respect for conscience. The necessity of advocacy for religious freedom being always in the context of human rights as a whole is highlighted.